PENGARUH PENGGUNAAN ZEOLIT SEBAGAI BAHAN PENGGANTI SEBAGIAN SEMEN TERHADAP KUAT TEKAN PAVING BLOCK KONVENSIONAL - Agung Rizki Pratomo; Fepy Supriani; Agustin Gunawan (Inersia: Jurnal Teknik Sipil, 2019)
This research was motivated by the contained SiO2 in zeolite. The purpose of this research was to know the zeolite effect as a substitute of cement in constructing 14 days paving block material which used conventional method toward the compressive strength of paving block. This research used SNI 03-06-1996 in constructing and testing the materials. The material was cube shaped with ±5 cm size which consists of normal paving block and 6 variations with 5 specimens of each variation. Total of specimen were 35. Substitute of zeolite variations used 2,5%, 5%, 7,5%, 10%, 12,5%, and 15% on the weight of cement. The result of compressive strength of normal paving block is 15,64 MPa. The result of compressive strength test had increased in the variation of 2,5% zeolite substitute by 6,28% normal paving block. The result of compressive strength test results showed the greatest decrease in variation of 15% zeolite replacement by 39,05% against normal paving block.